Risk Factors and Outcomes of Antibiotic-resistant Pseudomonas aeruginosa Bloodstream Infection in Adult Patients With Acute Leukemia. (23rd December 2020) - Zhao, Yuanqi; Lin, Qingsong; Liu, Li; Ma, Runzhi; Chen, Juan; Shen, Yuyan; Zhu, Guoqing; Jiang, Erlie; Mi, Yingchang; Han, Mingzhe; Wang, Jianxiang; Feng, Sizhou
Abstract: Background: Pseudomonas aeruginosa (PA) bloodstream infection (BSI) is a common complication in patients with acute leukemia (AL), and the prevalence of antibiotic-resistant strains poses a serious problem. However, there is limited information regarding antibiotic resistance, clinical characteristics, and outcomes of PA BSI in AL patients. This study explored characteristics associated with the clinical outcomes of AL patients with PA BSI and analyzed factors associated with BSI caused by multidrug-resistant (MDR) or carbapenem-resistant strains. Methods: This single-center retrospective study enrolled hospitalized AL patients who developed PA BSI during January 2014–December 2019. The Kaplan-Meier method was used to plot survival curves. Multivariate logistic regression analyses were also performed. Results: Of 293 eligible patients with PA BSI, 55 (18.8%) received inappropriate empirical antibiotic therapy within 48 hours of BSI onset, whereas up to 65.8% MDR-PA BSI patients received inappropriate empirical treatment. The 30-day mortality rate was 8.5% for all patients. However, the 30-day mortality rates were 28.9% and 5.5% in MDR-PA BSI and non–MDR-PA BSI patients, respectively ( P < .001). On multivariate analysis, previous use of quinolones (odds ratio [OR], 5.851 [95% confidence interval CI, 2.638–12.975]) and piperacillin/tazobactam (OR, 2.837 [95% CI, 1.151–6.994]) were independently associated with MDR-PA BSI; and MDR-PA BSI (OR, 7.196 [95% CI, 2.773–18.668]), perianal infection (OR, 4.079 [95% CI, 1.401–11.879]), pulmonary infection (OR, 3.028 [95% CI, 1.231–7.446]), and age ≥55 years (OR, 2.871 [95% CI, 1.057–7.799]) were independent risk factors for 30-day mortality. Conclusions: MDR increases mortality risk in PA BSI patients, and previous antibiotic exposure is important in MDR-PA BSI development. Rational antibiotic use based on local antimicrobial susceptibility and clinical characteristics can help reduce antibiotic resistance and mortality.